Bioactivity and structure–activity relationship of cinnamic acid derivatives and its heteroaromatic ring analogues as potential high-efficient acaricides against Psoroptes cuniculi. Issue 6 (1st April 2018) - Chen, Dong-Dong; Zhang, Bing-Yu; Liu, Xiu-Xiu; Li, Xing-Qiang; Yang, Xin-Juan; Zhou, Le
Graphical abstract: Abstract: A series of cinnamic acid derivatives and its heteroaromatic ring analogues were synthesized and evaluated for acaricidal activity in vitro against Psoroptes cuniculi, a mange mite. Among them, eight compounds showed the higher activity with median lethal concentrations (LC50 ) of 0.36–1.07 mM (60.4–192.1 µg/mL) and great potential for the development of novel acaricidal agent. Compound40 showed both the lowest LC50 value of 0.36 mM (60.4 µg/mL) and the smallest median lethal time (LT50 ) of 2.6 h at 4.5 mM, comparable with ivermectin [LC50  = 0.28 mM (247.4 µg/mL), LT50  = 8.9 h], an acaricidal drug standard. SAR analysis showed that the carbonyl group is crucial for the activity. The type and chain length of the alkoxy in the ester moiety and the steric hindrance near the ester group significantly influence the activity. The esters were more active than the corresponding thiol esters, amides, ketones or acids. Replacement of the phenyl group of cinnamic esters with α -pyridyl or α -furanyl significantly increase the activity. Thus, a series of cinnamic esters and its heteroaromatic ring analogues with excellent acaricidal activity emerged.